Evaluation of the dynamics of actors in the regulation of drug poisoning - Raúl José Martelo Gómez,; Piedad Mary Martelo Gómez,; Carlos Alberto Severiche Sierra, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article explores the power dynamics and strategic relationships among various actors in the regulation of drug poisonings using the MACTOR method. A total of eight actors were analyzed, including government regulatory agencies, healthcare institutions, the pharmaceutical industry, and the media, among others. The findings show that regulatory agencies have a positive influence on all objectives because their role is fully aligned with effective regulation and health system improvement, while healthcare institutions focus on reducing poisonings and strengthening pharmacovigilance. It is also evident that the regulation of drug poisonings requires a collaborative approach that considers the dynamics of influences, commitments, and strategic distances among actors. This study provides a comprehensive view of the system and highlights critical areas for improving the effectiveness of regulatory policies, contributing to safer and more sustainable drug management globally.